THE EFFECTIVENESS OF RUPBASAN ON STATE CONFISCATED PROPERTY CASE STUDY OF CLASS 1 CIREBON RUPBASAN - Ardiansyah Ardiansyah; Aprilia Maulani; Umair Umair; Tazqia Anandhita; Ade Jahasan (Ann Publisher, 2025)
Abstract Background. Indonesia guarantees the ownership of goods in the 1945 constitution, as stated in Article 28 H paragraph (4), which states that